ART access-related barriers faced by HIV-positive persons linked to care in southern Ghana: a mixed method study. Issue 1 (December 2016) - Ankomah, Augustine; Ganle, John; Lartey, Margaret; Kwara, Awewura; Nortey, Priscilla; Okyerefo, Michael; Laar, Amos
Abstract Background Timely and enduring access to antiretroviral therapy (ART) by HIV-infected individuals has been shown to substantially reduce HIV transmission risk, HIV-related morbidity and mortality. However, there is evidence that in addition to limited supply of antiretrovirals (ARVs) and linkage to ART in many low-income countries, HIV+ persons often encounter barriers in accessing ART-related services even in contexts where these services are freely available. In Ghana, limited research evidence exists regarding the barriers HIV+ persons already linked to ART face. This paper explores ART access–related barriers that HIV+ persons linked to care in southern Ghana face. Methods A mixed method study design, involving a cross-sectional survey and qualitative in-depth interviews, was conducted to collect data from four healthcare providers and a total of 540 adult HIV+ persons receiving ART at four treatment centres in Ghana. We used univariate analysis to generate descriptive tabulations for key variables from the survey. Data from qualitative in-depth interviews were thematically analysed. Results from the survey and in-depth interviews were brought together to illuminate the challenges of the HIV+ persons. Results All (100%) the HIV+ persons interviewed were ARV-exposed and linked to ART. Reasons for taking ARVs ranged from beliefs that they will suppress the HIV virus, desire to maintain good health and prolong life, and desire to prevent infection in unborn children, desire both to avoid death and to become good therapeutic citizens (abide by doctors' advice). Despite this, more than half of the study participants (63.3%) reported seven major factors as barriers hindering access to ART. These were high financial costs associated with accessing and receiving ART (26%), delays associated with receiving care from treatment centres (24%), shortage of drugs and other commodities (23%), stigma (8.8%), fear of side effects of taking ARVs (7.9%), job insecurity arising from regular leave of absence to receive ART (5.3%), and long distance to treatment centres (4.9%). Conclusions The results in this study suggest that efforts to provide and scale-up ART to all HIV+ persons must be accompanied by interventions that address structural and individual level access barriers.